Driving lean transport and logistics operations at Chandra Transport Corporation - Garza-Reyes, Jose Arturo; Balaji, Krishna (London : SAGE Publications: SAGE Business Cases Originals, 2022)
Lean Manufacturing was initially developed to improve manufacturing operations, but since its conception after the second world war by the Japanese car manufacturer Toyota, the application of the principles and techniques have expanded to other industries such as construction, healthcare, telecommunications, and food. This case study illustrates the adaptation and application of some lean principles and tools in the transport and logistics sector. Chandra Transport Corporation is a third-party logistics SME providing truck transportation services to paper manufacturers in the state of Tamil Nadu, India. It was looking to improve its operations and decided to follow the 'Lean route' to address, through waste reduction and efficiency improvement, the challenges posed by the transport and logistics sector of India and its operational issues.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Technological innovations -- India